LA EDUCACIÓN A DISTANCIA EN LAS UNIVERSIDADES DE AMÉRICA LATINA - Bustamante Sánchez, Yolanda (2005)
The objective of this research is to analyze the reality of long-distance education in different universities of Latin America. For this purpose we will observe its Institutional FODA in order to evaluate, compare and contrast on-line education vs. traditional education trying to identify the bases of education quality that can be applied on universities of our country.